Identifying Trends in Data Science Articles using Text Mining - Adil, S.H. (Institute of Electrical and Electronics Engineers Inc., 2019)
The research conducted in this paper presents a detailed analysis of the latest research publications related to Data Science using information retrieval and text mining approach. The database used in this study was created by collecting the latest research papers from well-reputed Journals and Conference proceedings published by IEEE and Springer. This comprehensive study shows the significance of information retrieval and text mining in the identification of key insight from textual documents. Â© 2019 IEEE.